Stunting Determinant Analysis in the East Mainland Province of East Nusa Tenggara for the Period of 2017-2021 - Picauly, Intje; P Manongga, Stefanus; Adar, Damianus; CH Liufeto, Franchy (Journal of Maternal and Child Health, 2022)
Background: The Mainland of Timor, East Nusa Tenggara Province (NTT) has a diverse regional topography with a high prevalence of stunting (>20%). The local government has taken preventive measures. However, the results show a very small reduction in the prevalence of stunting (±2-3%/year). This study aimed to determine the factors that influence the incidence of stunting in the Eastern Mainland Region, NTT Subjects and Method: This data was a cross-sectional study conducted in NTT, from in June to August 2022. A sample of 28 informants who were selected with the following considerations: officials from the Health Office, PUPR Service, Agriculture Service, and Regency/ City BPS data managers for the Eastern mainland region of NTT. The dependent variable was stunting. The independent variables were Availability of Public Health Workers, Infectious infectious diseases, Open defecation behavior, Family income level, Availability of clean water and proper sanitation, Exclusive breastfeeding, Posyandu visits, Program for giving iron tablets to young women, and Administration of Vitamin A. The data were analyzed by linear regression analysis. Results: Factors that influence the incidence of stunting were sanitation factors (b= -2.22; 95% CI= -3.52 to -0.91; p= 0.012), factor of pneumonia infection (b= 0.07; 95% CI= 0.01 to 0.13; p= 0.038), open defecation behavior factor (b= 2.60; 95% CI= 0.99 to 4.21; p= 0.014), and family income level factor (p= -1.21; 95% CI= -1.80 to -5.70; p= 0.009). Conclusion: The incidence of stunting in the East Mainland Region, NTT is influenced by factors: sanitation, pneumonia infection, open defecation behavior; and family income level. Keywords: stunting incidence, eastern mainland, sanitation factors, infectious diseases, pneumonia, open defecation. Correspondence:Intje Picauly, Department of Nutrition, Faculty of Public Health, Universitas Nusa Cendana, Kupang, Nusa Tenggara Timur, Indonesia, Jl. Adi Sucipto Penfui, Penfui, Maulafa, Kupang, Nusa Tenggara Timur.  Mobile: +62822-3714-5517. Email: intjepicauly@staf.undana.ac.id.